UPAYA MENINGKATKAN AKTIVITAS KETERAMPILAN MENULIS WACANA DESKRIPSI DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA SISWA KELAS XI LUKIS 1 SMK NEGERI 3 KASIHAN BANTUL - Fitria Herawati; Wijaya Heru Santosa (Universitas Sarjanawiyata Tamansiswa, 2016)
The purposes of the research are to describe (1) increased the activity of students in writing the discourse description using cooperative learning model type TAI and (2) increase students’ skills in writing discourse descriptions using cooperative learning model type TAI XI Lukis 1 SMK Negeri 3 Kasihan Bantul. Kind of this research is classroom action research which is held in two cycles. The research subject is all XI Lukis1 SMK Negeri 3 Kasihan Bantul students that contain 26 students. The object of this study is subject to the basic competence Indonesian write patterned narrative discourse description, descriptive, expository, and argumentative. The instrument that will be used is observation sheet, students, and teacher interview, test, and documentation The achievement data are analyzed in a qualitative way based on the reflection of every action cycle. The results of this study indicate that the TAI type of cooperative learning model can improve student learning activities in class XI Lukis 1 SMK Negeri 3 Kasihan Bantul on the process of learning to write discourse description. This is evident from the increased activity of students in each cycle. Students’ creativity in writing discourse description on pre-cycle 46,6%, cycle I 57,7%, and cycles II 69,23%. Students attention in paying attention to the teacher in pre-cycle 57,7%, the cycle I 69,23%, cycle II 76,9%. The attitude of the students in pre-cycle 65,38%,cycle I 73,1%, cycle II 84,6%. The students being active in a group discussion in pre-cycle 30,7%, the cycle I 38,5%, and cycle II 73,1%. Well cooperative in a group discussion of pre-cycle 53,8%, the cycle I 61,5%, and cycle II 92,3%. TAI type of cooperative learning model can improve the ability to write a description discourse of class XI Lukis 1 SMK Negeri 3 Kasihan Bantul. It is able to be seen from the aspect of idea contents in pre-cycle 26,92%, the cycle I 57,69%, and cycle II 92,30%. The idea organization accuracy in pre-cycle 38,46%, cycle I 69,23%, and cycle II 84,61%. The language order accuracy in pre-cycle 34,61%, cycle I 61,53%, and cycle II 84,61%. The use of vocabulary in pre-cycle 30,76%, the cycle I 65,38%, and cycle II 84,61%. The use of texts spelling in pre-cycle 34,61%, cycle I 69,23% and cycle II 92,30%.